The Effect of Donor Age on Structural and Mechanical Properties of Allograft Tendons. (February 2015) - Swank, Katherine R.; Behn, Anthony W.; Dragoo, Jason L.
Background: Allograft tendons are commonly used in surgical ligament reconstruction. While it is commonly accepted that donor age will affect mechanical properties of graft tissue, the apparent age threshold is unknown. Hypothesis: Donor age will significantly influence the structural and mechanical properties of tibialis posterior allograft tendons. Study Design: Controlled laboratory study. Methods: A total of 550 allograft posterior tibialis tendons were examined. Linear stiffness, ultimate tensile force, ultimate displacement, tensile modulus, ultimate tensile strength, and ultimate tensile strain were calculated for specimens from donors in each of 6 age groups: 15-29, 30-39, 40-49, 50-59, 60-69, and 70-79 years. Both first- and second-order polynomial regressions were performed to determine the correlation between structural and mechanical properties and age. Welch analyses of variance with Games-Howell post hoc tests were performed to facilitate comparisons among age groups. Results: All parameters displayed a weak correlation with age, with the highest R 2 term being 0.063 for ultimate tensile strength. Linear stiffness, ultimate tensile force, and tensile modulus displayed almost no correlation with age. Ultimate tensile strength increased slightly with age up to 40-49 years and then decreased with further increases in age. Slight decreases in ultimate displacement and ultimate tensile strain were observed with increasing age. Numerous statistically significant differences were observed between age groups for each outcome parameter; however, the magnitudes of the differences between age groups are relatively small (<15%) for all outcome parameters. Conclusion: Age explained at most 6% of the variation in structural and mechanical properties of tibialis posterior allograft tendons. Clinical Relevance: Posterior tibialis tendons from all age groups displayed structural properties superior to the native anterior cruciate ligament, with higher stiffness and ultimate force, and less displacement to failure. Although statistically significant differences in structural and mechanical properties were observed between age groups, the magnitudes of the differences are small and most likely not clinically relevant. The age of the donor will not likely affect the suitability of a graft for use in surgical reconstruction.